Intergenerational differences in the physical activity of UK South Asians - Bhatnagar, P (2014)
This thesis examines intergenerational change in prevalence of and attitudes to physical activity by comparing first and second-generation South Asians in Britain. British South Asians have poorer health outcomes including a higher prevalence of cardiovascular disease (CVD) and diabetes than White British people. Physical inactivity is one of the risk factors for CVD and diabetes. Physical activity levels are lower among British South Asians than the White British population, for reasons that include cultural factors related to being South Asian, the low socioeconomic status of some South Asian groups, and living in deprived neighbourhoods. However, existing literature on physical activity levels does not clearly distinguish between first and second-generations. Understanding generational differences in the influences on physical activity among South Asians is important for developing appropriate interventions. First, I review the existing quantitative and qualitative literature on physical activity in second-generation South Asians. There is some evidence that second-generation South Asians are more physically active than the first-generation. Despite this, second-generation South Asians remain less active than White British people. Neither the quantitative nor the qualitative literature has adequately explored the reasons for these findings. I then use data from the Health Survey for England to explore the ways that adult Indians, Pakistanis and Bangladeshis are physically active. When analysed by age and sex, all South Asians and the White British group were physically active in different ways to each other. However, there was little difference between younger Indians and younger White British people in the contribution of walking to total activity. Finally, I present a qualitative analysis of how ethnicity influences physical activity in second-generation South Asians. I interviewed 28 Indian women living in Manchester, England. I found that a British schooling and messages from the media had strongly influenced second-generation Indian women's attitudes to physical activity. Consequently, their motivations and barriers to physical activity were generally very similar to those reported for White British women. Second-generation Indian women had mostly adopted Western gender roles, with Indian gender expectations having a limited impact on their physical activity. In contrast, the traditional roles of Indian women constrained the leisure-time physical activity of the first-generation Indian women. There was no generational difference in how the local neighbourhood influenced physical activity. This thesis demonstrates clear differences in physical activity prevalence and attitudes between first and second-generation South Asian women in the UK. Interventions aimed at improving local environments for physical activity are likely to help all people living in deprived areas, regardless of ethnic background. Changing generic Western social norms around femininity and being physically active may be more important than tailored interventions for second-generation Indian women.